The Cultural Reality Of Human Resources And Its Relationship To Digitization - معمري, محمد (جامعة الوادي - University of Eloued, 2024)
The cultural values of human resources are among the most important factors on which the success and continuity of any form of development in the institution depends. The efficiency of institutions depends on the activation and investment of all their resources, in particular the human resources that control the rest of the resources, their direction and the way in which they are used. Therefore, the need for independent management of human resources has emerged. The cultural dimension, which is the sum of the common values that form the symbolic link between all elements of the organization, is a socio-cultural field where an organizational culture emerges and working groups are formed in harmony and effective with the organizational loyalty of the active individuals, and here it is clear that there is no organization without its human elements and energies. Technological development in the world of e-digitization of human resources in various organizations has become imperative and necessary. This is because of the nature of rapid and successive changes in human resources management in today's times. ICT encourages the establishment of "diverse polar networks", and organizational culture derives its characteristics from those of social culture, in which social culture and organizational culture share.
مقال
Keywords: Cultural reality, human resources, digitization, organizational culture